A SYSTEMATIC LITERATURE REVIEW OF FEAR OF MISSING OUT (FOMO) IN ECONOMIC ACTIVITIES: IMPLICATIONS FOR CONSUMER BEHAVIOR AND INDIVIDUAL PSYCHOLOGY - Nuraini, Fariha; Surya, Eka Putri; Rahmayanti, Dhita Aulia; Hesti, Mirna Shofa; Rosyida, Rosyida; Mukhlis, Imam; Agustin, Grisvia (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
FOMO (Fear of Missing Out) is a new concept in the study of individual behavior that can influence their decisions in terms of the economy. FOMO is also a study material that is widely mentioned in the financial media today. FOMO has an influential social component to post-decision regret, especially when individuals realize other choices are better made than uncertainty. This study aims to analyze the implications of FOMO in economic activity, especially for consumer behavior and market dynamics. This research uses the SLR (Systematic Literature Review) method in Scopus articles in 2020-2024 with the presentation of analysis through the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) model. Based on the results of predefined inclusion criteria, there are a total of 10 published articles in the last 5 years that analyze in detail about FOMO. These findings show that FOMO (Fear of Missing Out) has a relationship and influence on economic activity in terms of consumer decisions in purchasing investment, fashion products, cosmetics and luxury goods, as well as the use of technology. In addition, based on the results of SLR literature analysis using Watase Uake shows that there are grand theories related to FOMO variables, namely self-determination theory, social determination theory, and attachment theory. FOMO is a variable of economic psychology that exists in individuals at every age. The findings of this study can be a variable of social capital in further research on wise behavior, economics, and individual psychology.